A study on earnings management of zero-leverage firms from the perspective of financial constraints - Hyun-Ah Lee (Global Business & Finance Review (GBFR), 2022)
Purpose: This study verifies the debt covenant hypothesis by exploring the earnings management of zero-leverage firms that are not constrained by debt covenants. Furthermore, this study investigates whether the earnings management of zero-leverage firms varies depending on financial constraints, whether a consecutive zero-leverage period is associated with the level of earnings management, and whether this association varies depending on financial constraints. Design/methodology/approach: Using a sample of 5,669 firm-year data of listed firms in the securities market in South Korea from 2011 to 2019, this study conducts multiple regression analysis to examine the earnings management of zero-leverage firms from the perspective of financial constraints. In the analysis, two types of earnings management behaviors (i.e., accrual-based and real activities earnings management) are considered. Findings: The findings of this study show that zero-leverage firms are less likely to manage earnings than leveraged firms. Moreover, the longer the zero-leverage period, the lower the level of earnings management. However, these findings disappear when the analysis is conducted for firms with financial constraints. They indicate that a zero-leverage policy or a consecutive zero-leverage period is related to earnings management and that this relation varies depending on financial constraints. Research limitations/implications: This study provides insight into the attributes of zero-leverage firms by analyzing their earnings management. The findings of this study provide compelling evidence that zero-leverage firms are not homogeneous and are significantly distinct according to their status with or without financial constraints. Originality/value: This is the first study to test the debt covenant hypothesis by investigating the earnings management of zero-leverage firms. This study also extends the literature by examining the financing decisions that maintain zero leverage for a long period.
Keywords: 650; Zero-leverage; Leverage; Financial constraints; Debt covenants; Earnings management